LKB1 pathway and its role in cancer - Alessi, Dario (Henry Stewart Talks, 2011)
Mutations in LKB1 kinase cause Peutz Jeghers cancer syndrome, LKB1-activation and effects, LKB1/AMPK signaling pathway inhibits mTOR, Evaluating the role of LKB1 in regulating PTEN-induced tumourigenesis, AMPK-activators-mechanisms of action, AMPK-activators delay tumor onset in mice, Metformin as a useful drug in cancer prevention, The LKB1:STRAD:MO25 complex, Potential evolution of a pseudokinase, LKB activation by STRAD and MO25, Location of LKB1 cancer mutations, Activating protein kinases as a key challenge, Analysis of the NUAK protein kinase, Studying the role LKB1/NUAK1 signaling pathway in regulating cell adhesiveness and migration, Modeling the novel LKB1